Implementasi Action Research Dalam Perancangan Sistem Point Of Sale Dan Self-Ordering Berbasis Technology Acceptance Model Pada Coffee Pt.Kala Seduh - James A. Daulima; Geovani Rakha Firdaus; Rio Fikri Ramadhan; Muhammad Ridwan; Helina Dwi Ambarwati; Chahya Khairunnisa P; Siti Nurohmah; Istnadiya; Shafwah Nada (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
The rapid growth of the coffee shop industry demands service efficiency that conventional operational systems can no longer accommodate. Coffee Kala Seduh, operating under PT Kala Nusantara, faces critical obstacles in the form of customer queue accumulation during rush hours and discrepancies in raw material stock recapitulation caused by manual recording practices. This study aims to design and evaluate the level of user acceptance toward a QR-Code-based Point of Sale (POS) and Self-Ordering information system as a technological intervention to address these problems. The research employs a Mixed Methods approach with a Sequential Exploratory strategy, integrated with the Action Research cycle consisting of diagnosing, action planning, action taking, evaluating, and learning. System design was carried out through Context Diagram, Use Case Diagram, Activity Diagram, and Entity Relationship Diagram modeling, followed by the development of a high-fidelity interface prototype using Figma. The level of user acceptance was measured using a Technology Acceptance Model (TAM) questionnaire instrument comprising three dimensions, namely Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and User Satisfaction (SAT), distributed to 30 respondents through purposive sampling. The quantitative descriptive analysis yielded an actual score of 1,658 out of an ideal maximum score of 1,800, resulting in a feasibility percentage of 92.11%, which falls within the Very Good/Highly Feasible category. Qualitative findings from open-ended feedback further indicated the need for additional development, particularly a menu-note customization feature and an expanded range of e-wallet payment channels. This study concludes that the POS and Self-Ordering information system intervention is feasible for full implementation in the operations of Coffee Kala Seduh.